Türkiye’de para ikamesi ve para yaratma gelirleri - Yıldırım, Jülide (Afyon Kocatepe Üniversitesi, İktisadi ve İdari Bilimler Fakültesi Dergisi, 2000)
Ülkemizde yaklaşık son yirmi yıldır en önemli ekonomik sorun yüksek enflasyon olmuştur. Tasarruf sahiplerinin ellerinde bulundurdukları servetin değeri enflasyon karşısında eridiğinden, tasarruflarını enflasyon vergisinden korumak isteyen tasarruf sahipleri, para ikamesine giderek, Türk Lirası yerine ya da onunla birlikte yabancı para ve/veya yabancı para cinsinden mevduat bulundurmaya başlamışlardır. Bunun sonucu olarak Türk Lirasına olan talep ve hükümetin para yaratarak elde ettiği gelirde bir azalma beklenir. Bu çalışmada 1986-1999 döneminde Türkiye’de para ikamesi ve para yaratma gelirlerinin seyri incelenmiştir.

Inflation has been one of the major problems of Turkish economy for over twenty years. Even though monetary authorities claim that their major task is to figth inflation, high inflation rates provide money creation revenues for governments. However, the real value of Turkish Lira holdings of residents erodes, encouraging them to substitute the quickly depreciating Turkish Lira with a strong currency. When there is currency substitution in an economy, the demand for domestic money is expected to decrease. This, in turn, may lead to a reduction in the money creation revenues of the monetary authorities. In this study currency substitution and money creation revenues in Turkey are examined for the time period 1986- 1999.
Keywords: Para İkamesi; Türkiye; Para Yatırma